Penerapan Pembelajaran Matematika Realistik Berbantuan Media Digital Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Dharma Patra Sei Lepan - Nur Izhma Adzkia Zahra; Kairuddin Kairuddin (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to describe the improvement of mathematical problem-solving skills after applying the realistik mathematics learning assisted by digital media of class VIII students of SMP Dharma Patra Sei Lepan for the 2022/2023 academic year. The subjects in this study were 32 class VIII-A students of Dharma Patra Private Middle School. Data collection techniques used were teacher observation sheets, tests of mathematical problem-solving skills, and documentation. This research is a classroom action research (PTK) which consists of 2 cycles, each cycle consisting of 2 meetings. Before taking action, first given the initial test and at the end of each cycle is given a test of students' mathematical problem-solving abilities. The test results of students' mathematical problem-solving abilities increased from the initial test, cycle I, and cycle II. In the classical pre-test, 3 students (9.38%) passed and the average pre-test ability was 49.12% with a very low level of ability. In the first cycle test, there was an increase classically, 17 students (53.13%) completed and the average ability test obtained 69.01% with the ability level in the medium category. Then the second cycle test also experienced an increase in classically obtained 28 students (87.5%) completed and an average ability obtained 81.05% with a high level of ability category. Thus it can be concluded that the application of realistik mathematics learning assisted by digital media can improve the mathematical problem-solving skills of class VIII students of SMP Dharma Patra Sei Lepan.